The Old Testament : a brief introduction - Levin, Christoph, 1950- (Princeton, N.J. : Princeton University Press, 2005)
"No other book has influenced the religion and culture of the Western world like the Bible and its largest component, the Old Testament, which is shared by Jews and Christians alike. This book fully explains the development of the Old Testament canon, as well as the editorial history underlying its various parts, including the five books of Moses, the prophetic books, and the Psalms. Examining the Old Testament in its historical context, it also sheds new light on many of the shorter books, including Jonah, Job, Ruth, the Song of Solomon, Ecclesiastes, Esther, and Daniel." "Levin surveys fundamental changes that have taken place in Old Testament scholarship, noting that the accepted view of this part of the Bible has been called into question both by literary scholars and by archaeologists." "While the book treats the Old Testament as part of the cultural and religious history of the Ancient Near East, it also reminds readers that it emerged not as a history of ancient Israel but as the Holy Scripture of Judaism. It will prove a compelling read for anyone interested in the history of religion and the history of ancient Israel."--BOOK JACKET.
Why read the Old Testament? -- Ch. 1. "Not a dot, nor a tittle shall pass" : the text of the Old Testament -- Ch. 2. A book as library : the Old Testament canon -- Ch. 3. The Old Testament as holy scripture passed down by postexilic Judaism -- Ch. 4. The remnants of ancient Israelite literature -- Ch. 5. The great redactions of the sixth century B.C.E. -- Ch. 6. The beginnings of Old Testament theology : the book of Jeremiah -- Ch. 7. The theological significance of the law -- Ch. 8. The struggle for precedence between the theologians from the exile and the Jerusalem temple school : the book of Ezekiel -- Ch. 9. The temple as the center of the Jewish diaspora : the priestly source -- Ch. 10. Fixing the Torah : the Pentateuch radaction -- Ch. 11. The modification of kingship theology : second Isaiah -- Ch. 12. Prophetic eschatology : the book of Isaiah -- Ch. 13. The conflict with the proto-Samaritan community : the book of Hosea -- Ch. 14. Judaism on the threshold of the Hellenistic age : the chronicler's history -- Ch. 15. Sects and groups within Hellenistic Judaism -- Ch. 16. Didactic stories -- Ch. 17. On the fringe of the canon -- Ch. 18. The Maccabean period and the rise of apocalyptic : the book of Daniel -- Ch. 19. The close of the canon -- Ch. 20. The Old Testament : an open book -- App. A. The books of the Old Testament -- App. B. The Hebrew Bible -- App. C. The Septuagint.
Includes bibliographical references (p. [187]-191).
Keywords: Bible. -- Commentaries